Analisis Kepuasan Pengguna BIMA Menggunakan Integrasi Model EUCS Delone Mclean dan Self-Efficacy - Nurul Fitriani; Sarah Astiti; Rona Nisa Sofia Amriza (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
Technology modernization is developing so fast that people have become dependent on it. Technology has a major impact on human life. It plays a larger role in the life of a wider community, especially in education, where it plays a role as a knowledge provider. The information system is an integrated unit of information technology and an activity to support operations and management to use the technology. One of the information systems used in education is the Research and Community Service Information Base (BIMA). BIMA is an information system that reports research activities such as planning, implementation, and reporting. BIMA implementation is within the Academic Community of the Telkom Purwokerto Institute of Technology. However, BIMA still has several problems with the infrastructure and systems, creating dissatisfaction when users access it. Based on these conditions, an analysis of user satisfaction with BIMA is needed. This study uses the EUCS, Delone Mclean, and Self-Efficacy Model Integration. This study analyzes user satisfaction levels and determines which factors significantly affect BIMA user satisfaction. The testing technique used is SEM-PLS. Based on the test results, there are five variables with a significant effect. Information Quality, System Quality, and Self-Efficacy significantly affected User Satisfaction. Technical Support significantly affected System Quality, and System Quality variables significantly affected Information Quality. One hypothesis has no significant effect on User Satisfaction, namely the Technical Support variable with p-values > 0.05, which is 0.478 and the t-statistic value <1.64, which is 0.032.